Calvin’s Concept of the Church as mater fidelium (Mother of Believers), Viewed through His Concept of Accommodation - Cha, Jaeseung (Journal of reformed theology, 2015)
Is the church distinctive from us or are we ourselves the church? Unlike many protestant believers who understand the church as assembly of believers, Calvin defines the church as mater fidelium (mother of believers), just as the Catechism of Catholic Church describes, following Cyprian. To review in what ways Calvin’s view is similar to—and differentiated from—that of Catholicism, this article discusses the concept of the church as ‘Mother’ in the early church, focusing on Tertullian, Cyprian, and Augustine. Then, it deals with Calvin’s concept of mater fidelium and move on to Calvin’s concept of accommodation in his ecclesiology. It concludes that Calvin’s use of the concept in four different ways is similar to Augustine’s rather than to Cyprian’s, and that Calvin’s concept of accommodation as God’s relationship to the church can overcome the tension between the church as ‘mother of believers’ and the church as ‘believers themselves.’